Effects of carbon dioxide gas on flammability limits of LPG - Nursyilla, Mohd Fauzi (2012)
Liquefied petroleum gas or LPG has well acknowledged as an attractive source of fuel in these centuries as it has provided us evidence to be the most effective and environmental friendly among all other fuel existed. However,like the other fuel,LPG also has its own benefits and drawbacks at when it is inadequately treated can be destructive to us.After knowing the characteristics of LPG and recognizing suitable ways of reducing risks in storage, handling and transportation of it, an appropriately planned experiment has been carried out. Specifically,this study is conducted to study the effect of carbon dioxide (CO2)to the Lower Flammability Limit(LFL)and Upper Flammability Limit (UFL) of LPG. LFL and UFL create a range at which explosion may occur to any flammable substance. By adding diluents (in this case isCO2)to the LPG-air mixture,the range was predicted to be narrowed down because the role of diluents to the mixture is to reduce the concentration of oxygen(O2) existed in the mixture to a level where explosion can be stopped.The most proper equipment to be used in order to achieve the objective of the study is the 20-L-Explosion Vessel.Only by using this high-tech equipment-the experiments,which involving explosion, can be safely performed.In the experiment,different volume percentage of CO2 was added in the pre-mixed LPG-air mixture.Three sets of experiments were done in order to compare the effect of CO2 addition in the pre-mixed LPG-air mixture towards its flammability limit respectively. Fortunately, the results were moderately following the theories where the range of flammability limit of LPG - air mixture was fruitfully reduced from 4.2 % vol.To 3 % vol.of LPG.